PERSEPSI WANITA PELAKU PERNIKAHAN DINI TENTANG HIV/AIDS DI DUSUN PECINAN DESA BESUKI KECAMATAN BESUKI KABUPATEN SITUBONDO - Zainuri, Imam; Andryani Mahrufi, Nurul (JURNAL KEPERAWATAN BINA SEHAT, 2014)
The main reason that underlied early marriage generally was to avoid the risk of free sex and coexisting diseases, but in fact teenagers who had been married more at risk for contracting sexually transmitted diseases, especially HIV than unmarried ones. Early marriages were still rampant, one of the reasons due to negative perception in looking at the risk of HIV infection. The purpose of this research was to know the perception of women who did early marriage about HIV/AIDS in Pecinan Sub Village Besuki Village Besuki Sub District Situbondo District. Research design was descriptive with population were all women who did early marriage as many as 64 people and obtained 56 respondents as samples who were taken by using purposive sampling. Variable was the perception of women who did early marriage about HIV/AIDS. Data obtained by using instruments such as questionnaires which spreaded on 24 July to 9 August 2014 then it presented in the form of frequency distribution table. The results showed the majority of respondents had negative perceptions about HIV/AIDS as many as 33 respondents (58,9%). Negative perception was influenced by several factors, including their average age were still very young, as housewife, had elementary education, and lack of the right information about HIV/AIDS. Mothers should seek additional information about HIV/AIDS from many sources of information. Local Health Authority should increase coordination with other health provider regarding the various risks of early marriage, especially HIV/AIDS primarily for teenagers who were at risk of early marriage through the school health program and the parents of teenage girls.Keywords: perception, women who did early marriage, HIV/AIDS